Aging and Contralateral Suppression Effects on Transient Evoked Otoacoustic Emissions - Parthasarathy, Teralandur K. (Journal of the American Academy of Audiology, 2001)
Transient evoked otoacoustic emissions (TEOAEs) were recorded in 30 normal-hearing subjects to nonlinear clicks while continuous contralateral broadband noise (CBBN) was presented at 40, 50, 60, and 70 dB HL. Thirty subjects between 20 and 79 years were divided systematically into six-decade age groups, five subjects per group. All subjects in each group had hearing thresholds of 20 dB HL or better for the test frequencies from 0.25 to 8.0 kHz and normal acoustic immittance findings. The results provide evidence that contralateral suppression at varying levels of CBBN is interactive with age. Except for subjects in the age ranges between 60 and 69 and 70 and 79 years of age, an increase in CBBN from 40 to 70 dB in 10–dB steps resulted in an average increase in suppression from about 0.5 to 3.5 dB SPL. In addition, the contralateral suppression at 60 and 70 dB HL was significantly greater for subjects between 20 and 59 years of age than for subjects between 60 and 79 years of age.Abbreviations: ANOVA = analysis of variance, CAP = compound action potential, CBBN = contralateral broadband noise, CNS = central nervous system, MOS = medial olivocochlear system, OAEs = otoacoustic emissions, OHCs = outer hair cells, TEOAEs = transient evoked otoacoustic emissions
Keywords: Aging; otoacoustic emissions; outer hair cells; peripheral hearing loss; suppression effect